2015
DOI: 10.1016/j.dr.2014.12.004
|View full text |Cite
|
Sign up to set email alerts
|

Affordances and limitations of electronic storybooks for young children's emergent literacy

Abstract: A B S T R A C TStories presented on phones, tablets and e-readers now offer an alternative to print books. The fundamental challenge has become to specify when and for whom the manner in which children retain information from stories has been changed by electronic storybooks, for better and for worse. We review the effects of digitized presentations of narratives that include oral text as well as multimedia information sources (e.g., animations and other visual and sound effects, background music, hotspots, ga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
185
1
9

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 295 publications
(203 citation statements)
references
References 80 publications
8
185
1
9
Order By: Relevance
“…16 Digital books (also called "eBooks, " books that can be read on a screen) often come with interactive enhancements that, research suggests, may decrease child comprehension of content or parent dialogic reading interactions when visual effects are distracting. 17 Parents should, therefore, be instructed to interact with children during eBook reading, as they would a print book.…”
Section: Preschool Media and Learningmentioning
confidence: 99%
“…16 Digital books (also called "eBooks, " books that can be read on a screen) often come with interactive enhancements that, research suggests, may decrease child comprehension of content or parent dialogic reading interactions when visual effects are distracting. 17 Parents should, therefore, be instructed to interact with children during eBook reading, as they would a print book.…”
Section: Preschool Media and Learningmentioning
confidence: 99%
“…Kao et al (2016) et al, (2012) feito com 137 ebooks infantis mais populares nos EUA em 2012, 75% continham hostpost, mas apenas 20% das áreas interativas tinham alguma relação com a história. Contudo, hotspots apesar de serem geralmente empregados para entretenimento, podem também ser úteis em fornecer ajuda, como por exemplo na habilitação de dicionário para palavras difíceis no texto TAKACS;KEGEL 2015, p. 80). Hotspots bem concebidos, congruentes ao conteúdo literário, tendem a proporcionar livros mais atraentes às crianças para a realização da tarefa de leitura (CAHILL; MCGILL-FRANZEN, 2013).…”
Section: Recomendações Para O Design De Interfaces De Liasunclassified
“…De acordo com as referências analisadas, além da seleção criteriosa de livros infantis digitais, também o correto uso destes são funções atribuídas como responsabilidade do mediador de leitura -pais, ou professores -. (MORGAN, 2013) Contudo, livros digitais altamente interativos podem oferecer uma mediação de leitura frustrante entre mediadores e crianças, já que ao tentar ler as histórias os adultos acabam interferindo, inclusive erroneamente, nas áreas de interação (BUS; TAKACS; KEGEL, 2015). Do ponto de vista do Design, esta questão revela sérios problemas projetuais, pois significa que estes artefatos não cumprem propriamente com a sua finalidade em uma tarefa padrão, como no caso de leitura entre pais e filhos.…”
Section: Considerações Finais E Desdobramentosunclassified
“…It is suggested that such features necessitate skills and abilities like task switching, which involve an excessive cognitive load that may have negative consequences for story comprehension (e.g. Bus, Takacs, & Kegel, 2014). At the same time, multimedia additions such as visual illustrations or other non-verbal information that work in harmony with the narration have been shown to improve children's story comprehension (e.g.…”
Section: E-book Activities In Early Childhood Educationmentioning
confidence: 99%